To study the clinical profile of dengue fever and to evolve a prognostic marker based on hematological parameters for severe dengue - Sivathanu, Shobhana; Manickam, Kumar; Sampath, Sowmya; Nagaraj, Poornima; Kumar, Sathish Kumar Sunder; Pachaimuthu, Ramakrishnan A. (International Journal of Contemporary Pediatrics, 2017)
Background: Dengue fever is endemic to most parts of India and the clinical recognition of progression to severe dengue may become difficult in the absence of classical findings. Early recognition of shock or hemorrhage and appropriate management with fluids prevents morbidity/mortality to a great extent. In this study, we attempted to evolve a simple hematological prognostic marker for prediction of severe dengue. Methods: This retrospective descriptive study of 67 children was conducted in the Paediatric Department of a Government Medical College. The case records of all the patients with a diagnosis of dengue fever and Severe Dengue were analysed using a preset proforma. Besides the demographic and clinical findings a detailed analysis and comparison of hematological profile was done between cases of dengue fever and severe dengue. The data obtained was analysed statistically in order to arrive at a hematological marker to predict severe dengue. Results: Study population consisted of 67 children with 44 children with dengue fever,12 with DSS and 11 cases with DHF. Detailed analysis of hematological profile of severe dengue showed striking neutrophilia and monocytosis besides thrombocytopenia. Neutrophilia was seen in 78% and monocytosis was prevalent in 91% of cases of severe dengue. Monocytosis with thrombocytopenia was consistently seen during shock/hemorrhage. During recovery the fall of monocytes was accompanied by simultaneous increase in platelets in this group. This inverse relation was found to be statistically significant (p <0.05) Such a significant inverse correlation was not seen in dengue fever group (p >0.05). Conclusions: Monocytosis and neutophilia are consistent features of dengue fever. There is an inverse correlation of monocytosis with thrombocytopenia in severe dengue during shock/hemorrhage which recovers on clinical improvement. Thus monocytosis with thrombocytopenia can be used as a prognostic marker to predict severe dengue.